2009
DOI: 10.1073/pnas.0812256106
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of p53 by IκB kinase 2 promotes its degradation by β-TrCP

Abstract: Functional inactivation of p53 and constitutive activation of the NF-B pathway has been associated with several human cancers. In this study, we show that I B kinase 2 (IKK2/IKK␤), which is critical for NF-B activation, also phosphorylates p53. Phosphorylation of p53 at serines 362 and 366 by IKK2 leads to its recruitment to and ubiquitination by ␤-TrCP1. Degradation of ubiquitinated p53 is independent of Mdm2, because it occurs in both wild-type and Mdm2 ؊/؊ cells. SiRNA-mediated reduction in the levels of ␤-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(135 citation statements)
references
References 43 publications
5
124
2
4
Order By: Relevance
“…A model can be proposed in which the activation of the mechanisms responsible for IKK␣ or IKK␤ nuclear accumulation favor apoptosis or proliferation via stabilization of TAp73 or ⌬Np73␣, respectively. Interestingly, an additional study has recently shown that IKK␤ phosphorylates p53 at two specific serines, promoting its ubiquitination and degradation by ␤-TrCP1 and independently of MDM2 and NF-B (31). Taking into consideration our data and those of Xia's study (31), IKK␤ appears to modulate p53 transcriptional activity through two independent mechanisms, the first promoting its phosphorylation and destabilization and the second inducing phosphorylation and accumulation of the p53 antagonist ⌬Np73␣.…”
Section: Discussionmentioning
confidence: 75%
“…A model can be proposed in which the activation of the mechanisms responsible for IKK␣ or IKK␤ nuclear accumulation favor apoptosis or proliferation via stabilization of TAp73 or ⌬Np73␣, respectively. Interestingly, an additional study has recently shown that IKK␤ phosphorylates p53 at two specific serines, promoting its ubiquitination and degradation by ␤-TrCP1 and independently of MDM2 and NF-B (31). Taking into consideration our data and those of Xia's study (31), IKK␤ appears to modulate p53 transcriptional activity through two independent mechanisms, the first promoting its phosphorylation and destabilization and the second inducing phosphorylation and accumulation of the p53 antagonist ⌬Np73␣.…”
Section: Discussionmentioning
confidence: 75%
“…Ikkβ may play a role in the regulation of p53-mediated gene expression, through a mechanism whereby phosphorylated p65 stably associates with p53 at p53 responsive promoters, resulting in an inhibition of p53-mediated transcriptional activity (66,67). Alternatively, Ikkβ may directly phosphorylate p53 on serines 362 and 366 to promote its turnover (68). Here, we show that Ikkb knockout in melanocytes increased p53 protein levels.…”
Section: Discussionmentioning
confidence: 75%
“…Another relevant study showed that IKKβ, a major component and mediator of the conventional NF-κB pathway, can phosphorylate p53, leading to its ubiquitination and degradation independent of Mdm2. 50 Thus, it is possible that IKK, which is constitutively activated by extrinsic mediators of chronic inflammation (cytokines), might cause long-term inhibition of p53 activity. Products of NF-κB-responsive genes can also suppress p53 function by acting against its downstream targets: For example, NF-κB-induced anti-apoptotic factors can neutralize the effects of pro-apoptotic products induced by p53.…”
Section: Reciprocal Negative Regulation Of P53 and Nf-κbmentioning
confidence: 99%